Vessel-Bridge Collision Reliability Assessment Based on Structural Dynamic Analysis - Fu Tao; Ren Xiaoqian; Wang Kai (Advances in Civil Engineering)
Reliability analysis of vessel-bridge collision plays an important role in the construction of inland bridges. In this paper, a new method is proposed based on structural dynamic analysis. The random characteristics of three factors—impact angle, deadweight tonnage of vessels, and impact velocity—are considered. This method combines the method of moments with nonlinear dynamic finite element analysis, which can enhance the efficiency of calculating failure probability.